17. ASSOCIATION RELATED TO RESILIENCE COPING SKILL AMONG INPATIENTS WITH DEPRESSION AT NATIONAL INSTITUTE OF MENTAL HEALTH, BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the resilience level and identify relevant facors in hospitalized depressive patients at the National Institute of Mental Health – Bach Mai hospital.Methods: A cross-sectional descriptive study was conducted on 256 hospitalized depressive patients at the National Institute of Mental Health – Bach Mai Hospital from October 2021 to April 2022. The study used the Brief Resilient Coping Scale (BRCS) to estimate the level of resilience in patients with depression.Results: The average age of the study group was 36.1 ± 16.2 years. The male-to-female ratio was 1:3.6. Among the patients, 52,4% had a university education, and nearly 48,4% were married and living with their families or partners. 87.4% of the patients had low to moderate resilience coping skill. The group under 35 years old, having a university degree, being unmarried, and having a lower level of psychological stress had a higher resilience coping skill than the rest.Conclusion: Patients aged 18-34 have better resilience than those over 35. The higher the level of psychological stress, the lower the resilience. Negative emotions are positively correlated, relatively closely, with the resilience of depressed patients.
Keywords: Depression; resilience coping skill; psychological distress